Melting temperature measurement and mesoscopic evaluation of single, double and triple DNA mismatches. Issue 31 (30th July 2020) - Oliveira, Luciana M.; Long, Adam S.; Brown, Tom; Fox, Keith R.; Weber, Gerald
Abstract : A comprehensive experimental and theoretical evaluation of all DNA mismatch contexts, providing an insight into the intra-molecular interactions. Abstract : Unlike the canonical base pairs AT and GC, the molecular properties of mismatches such as hydrogen bonding and stacking interactions are strongly dependent on the identity of the neighbouring base pairs. As a result, due to the sheer number of possible combinations of mismatches and flanking base pairs, only a fraction of these have been studied in varying experiments or theoretical models. Here, we report on the melting temperature measurement and mesoscopic analysis of contiguous DNA mismatches in nearest-neighbours and next-nearest neighbour contexts. A total of 4032 different mismatch combinations, including single, double and triple mismatches were covered. These were compared with 64 sequences containing all combinations of canonical base pairs in the same location under the same conditions. For a substantial number of single mismatch configurations, 15%, the measured melting temperatures were higher than the least stable AT base pair. The mesoscopic calculation, using the Peyrard–Bishop model, was performed on the set of 4096 sequences, and resulted in estimates of on-site and nearest-neighbour interactions that can be correlated to hydrogen bonding and base stacking. Our results confirm many of the known properties of mismatches, including the peculiar sheared stacking of tandem GA mismatches. More intriguingly, it also reveals that a number of mismatches present strong hydrogen bonding when flanked on both sites by other mismatches. To highlight the applicability of our results, we discuss a number of practical situations such as enzyme binding affinities, thymine DNA glycosylase repair activity, and trinucleotide repeat expansions.